A Study in Data Security in Cloud Computing - Mazlina, Abdul Majid; Jaber, Aws Naser; Mohamad Fadli, Zolkipli; Khan, Nusrat Ullah (2014)
The vision of 21st century computing is that users can access Internet services over lightweight portable devices rather than via variants of the traditional desktop computer. Consequently, users will have no interest in large, powerful machines. How, then, will computing power be provided? The answer to this question lies in cloud computing. Cloud computing is a recent trend in IT in which computing power and knowledge are moved away from the desktop and desktop PCs into giant datacenters. In the cloud computing paradigm, applications are delivered as services over the Internet. The key driving forces behind cloud computing are the presence of broadband and wireless networking, falling storage prices, and progressive enhancements in Internet computing software packages. Cloud service shoppers can add additional capabilities at peak demand, reduce prices, experiment with new services, and remove unessential capabilities. Service suppliers can increase utilization via multiplexing and allow for larger investments in software packages and hardware.